Dimensions of Prym varieties - Amy E. Ksir (International Journal of Mathematics and Mathematical Sciences)
Given a tame Galois branched cover of curves π:X→Y with any finite Galois group G whose representations are rational, we compute the dimension of the (generalized) Prym variety Prymρ(X) corresponding to any irreducible representation ρ of G. This formula can be applied to the study of algebraic integrable systems using Lax pairs, in particular systems associated with Seiberg-Witten theory. However, the formula is much more general and its computation and proof are entirely algebraic.